The biological response modifier AM3 attenuates the inflammatory cell response and hepatic fibrosis in rats with biliary cirrhosis. Issue 7 (4th May 2010) - Albillos, Agustín; Nieto, Mónica; Ubeda, María; Muñoz, Leticia; Fraile, Benito; Reyes, Eduardo; Lledó, Lourdes; Blanco, Ignacio; Pastor, Óscar; Salas, Clara; Lario, Margaret; Monserrat, Jorge; et al.
Abstract : Background: An inflammatory immune system response ensues in the liver and in the systemic circulation in cirrhosis, where it contributes to hepatic fibrosis and peripheral vasodilation. Modulation of the inflammatory response without increasing susceptibility to infection is a therapeutic target in cirrhosis. AM3 is a low-toxicity biological response modifier with regulatory effects on innate and adaptative immunity, and the ability to normalise the production of tumour necrosis factor α (TNFα). Aims: This was an experimental study to investigate the effects of oral AM3 on the systemic and hepatic inflammatory response, liver fibrosis and on the haemodynamic abnormalities of portal hypertension in rats with biliary cirrhosis. Design: Bile-duct ligated rats received a 3-week oral course of AM3 or placebo. Results: In cirrhotic rats, AM3 blunted the inflammatory switch of circulating and intrahepatic monocytes and T-cells to TNFα and interferon γ (IFNγ) production, respectively. AM3 modified the intrahepatic polarisation pattern of the regulatory cytokines, decreasing the mRNA expression of transforming growth factor β1 (TGFβ1), interleukin 4 (IL4), and IFNγ, and increasing that of IL10. Total and IFNγ-producing natural killer (NK) cells were lowered by AM3 in the peripheral blood and liver of cirrhotic rats. The immunomodulatory effects of AM3 led to reduced hepatic fibrogenesis in cirrhotic rats, as shown by decreased area of liver fibrosis, hydroxyproline content and mRNA expression of procollagen α1(I). Besides, AM3 lowered portal pressure and systemic hyperaemia. Conclusions: The biological response modifier AM3 reverses the concurrent inflammatory immune system activation in peripheral blood and liver of experimental established cirrhosis, which results in reductions of hepatic fibrosis, portal pressure and peripheral vasodilation.